OTHERNESS REPRESENTATION: A POSTCOLONIAL ANALYSIS OF TARZAN OF THE APES - Ntamwana, Simon; Neba, Divine Che (Sanata Dharma University, 2024)
This paper investigates the question of representation in Burroughs Tarzan of the Apes. It probes into the representation of otherness, with a focus on the signification of race, religion, and gender. Written against the backdrop of postcolonialism, the paper contends that the construction of the black other, religious discrimination, and female inferiority by Western imperialists and patriarchy prefigure persistent domination in the new world order. In this qualitative descriptive study that is based on textual analysis as a research method, the primary data were collected from the novel Tarzan of the Apes. Concerning secondary data, articles and books pertinent to postcolonial studies and popular literature were consulted. It was discovered that blacks are represented as the unorthodox religious other embodying evil, darkness, ignorance, and primitive sensualism. Moreover, the black woman is pushed to the periphery and represented as a subject of barbarous polygamy, uncontrolled birth, and toys to satisfy mens desires. Furthermore, blacks are represented as hairless apes that are incapable of civilization. Finally, we discovered that the issue of the black other in particular was not a mistake by imperialists, but a well-planned scheme to concretize all the different forms of domination listed above, including the colonial agenda.